New records of Leptuca tallanica (Brachyura, Ocypodidae) in the Parita Gulf, Panama, Pacific - Roberto Lombardo (Revista Peruana de Biología)
We present the first report of the Peruvian Fiddler Crab, Leptuca tallanica (von Hagen, 1968), in Panama. The species identification from two sites in the Parita Gulf was confirmed by the presence of a moderately wide front, comma-shaped patches of pile on the male carapace, a pilous triangular depression at the base of the pollex, and a strong, tuberculate projection subdistally on the pollex. Our findings extend the previously known distribution range in the eastern Pacific from southern Ecuador and northern Peru northward to Panama.